Algumas diretrizes estatísticas para a avaliação do erro do método na mensuração de variável quantitativa - Mendes, Ary José Dias [UNESP]; Santos-pinto, Ary Dos [UNESP] (Dental Press Editora, 2007)
INTRODUCTION: the method error must be quantified to support the validity of the research and its clinical application. The determination of the reliability of the landmark identification to obtain measurements constitutes a fundamental precondition for a correct interpretation and utilization of the data. Each observed measurement can be analyzed through its actual value and its error component. The reliability is verified through repeated measurements. AIM: the purpose of this paper was to describe a statistical method which allows the researcher to verify if the measurements which he obtained at a certain moment are repeated by him at a posterior moment. This method confirms the non occurrence of the systematic error and allows an evaluation of the occurrence of the casual error, always presents in any form of measurement. Also, it presents the application of this statistical method in data referring to two cephalometric measurements and shows the syntax for the resolution of the method error through the use of the SPSS software for computers.

INTRODUÇÃO: o erro do método deve ser quantificado para fundamentar a validade da pesquisa e sua aplicação clínica. A determinação da confiabilidade na identificação dos pontos de referência para a obtenção de medidas constitui pré-requisito fundamental para uma interpretação segura e utilização correta dos dados obtidos. Cada medida observada pode ser analisada pelo seu valor real e pela sua componente de erro. A confiabilidade é verificada a partir de medidas repetidas. OBJETIVO: o propósito deste trabalho é descrever um método estatístico que permita que o pesquisador verifique se as mensurações que realizou num certo momento são repetidas por ele num momento posterior. Este método confirma a não ocorrência do erro sistemático e permite uma avaliação da ocorrência do erro casual, que está sempre presente em qualquer forma de mensuração. Apresenta a aplicação deste método estatístico em dados referentes a duas medidas cefalométricas e aponta uma sintaxe para resolução do erro de método a partir do uso do programa SPSS® para microcomputador.
Some statistical directions for the evaluation of the method error when measuring a quantitative variable
Keywords: Method error; Statistics; Cephalometry; Reliability; Erro do método; Estatística; Cefalometria; Confiabilidade